Influence of additional cement augmentation on endplate stability in circumferential stabilisation of osteoporotic spine fractures. (August 2019) - Herren, Christian; Quast, Kathrin; Prescher, Andreas; Fischer, Horst; Thüring, Johannes; Siewe, Jan; Hildebrand, Frank; Greven, Johannes; Kobbe, Philipp; Pishnamaz, Miguel
Abstract: Background: Anterior stabilisation of osteoporotic spine fractures is uncommon but necessary in the case of complex vertebral body comminution. The purpose of this study was to investigate the effect of additional cement-augmentation on the endplate stability. Methods: Twelve human cadaveric lumbar spines were divided in two groups: (A) posterior cement-augmented pedicle screw/rod-based instrumentation of L3 to L5, posterior decompression of L4/5 and partial corpectomy of L4 and (B) same experimental setup with additional cement-augmentation of the adjacent endplates. A cyclic loading test was performed at a frequency of 3 Hz, starting with a peak of 500 N for the first 2.000 cycles, up to 950 N for 100.000 cycles under a general preload with 50 N. All specimens were evaluated with regard to a potential collapse of the adjacent endplates. Subsequently, the maximum zero-time failure load of all specimens was determined using a universal testing machine. Findings: The median T-score of bone density was −4.32 (range −2.97 to −5.59), distributed equally in the two groups (average age 83 years). The specimen of the endplate-augmented group showed a significant higher failure load compared to non-endplate-augmented cadavers (group A: 2038 N, group B: 2990 N, p = 0.03). All specimens passed the full cyclic loading protocol with 100.000 cycles. No significant difference was observable regarding the adjacent endplate subsidence. Interpretation: Additional cement augmentation in circumferential stabilisation resulted in a significant enhancement of the endplate stability regarding the maximum axial load, while the cyclic loading did not significantly enhance the fatigue endurance of the vertebral endplates over the 100, 000 cycles tested. Highlights: Cement augmentation of the cage endplates is possible under fluoroscopic guidance. The specimen of the endplate-augmented group showed a significant higher failure load. No significant difference was observable regarding the adjacent endplate subsidence. The indication for cage implantation in the osteoporotic spine is rare and should be well-chosen.